Numerical Investigation of Depressurization through Horizontal Wells in Methane-Hydrate-Bearing Sediments Considering Sand Production - Xuyang Guo; Yan Jin; Jingyu Zi; Jiaying Lin; Bolong Zhu; Qian Wen; Qi Jing (Journal of Marine Science and Engineering, 2022)
Sand production has been identified as a key reason limiting sustained and commercial gas production in methane-hydrate-bearing sediments. Production tests in Canada and Japan were terminated partially because of excessive sand production in pilot wells. It is meaningful to carry out numerical investigations and sensitivity analyses to improve the understanding of sand production mechanisms during the exploitation of methane hydrates. This study introduces a numerical model to describe the coupled thermal–hydraulic–mechanical–chemical responses and sand production patterns during horizontal well depressurization in methane-hydrate-bearing sediments. The model is benchmarked with a variety of methane hydrate reservoir simulators. Results show that the spatial and temporal evolution patterns of multi-physical fields are different and the hydromechanical evolutions are the fastest. Gas production and sand production rates are oscillatory in the early stages and long-term rates become stable. Gas production is sensitive to rock physical and operational parameters and insensitive to rock mechanical properties such as cohesion. In contrast, sand production is sensitive to cohesion and insensitive to rock physical and operational parameters. Although cohesion does not directly affect gas productivity, gas productivity can be impaired if excessive sand production impedes production operations. This study provides insights into the sand production mechanism and quantifies how relevant parameters affect sand production during the depressurization in methane-hydrate-bearing sediments.